PENGEMBANGAN PARIWISATA DI DESA WISATA LEREP KABUPATEN SEMARANG (TINJAUAN DIMENSI ATRAKSI AKTIVITAS AKSESIBILITAS DAN AMENITAS) - Hanafi, Muhammad; Yuniningsih, Tri; Hayu Dwimawanti, Ida (Journal of Public Policy and Management Review, 2025)
This study aims to analyze the development of tourism in Lerep Tourism Village, Semarang Regency, using the 4A dimensions: attractions, activities, accessibility, and amenities. Lerep Tourism Village holds great potential in tourism based on local wisdom, including natural, cultural, educational, and creative tourism. However, the development of tourism in this village faces several challenges, such as inadequate infrastructure, lack of promotion, and limited coordination among stakeholders. The research employs a qualitative descriptive method, with data collected through observation, interviews, and document studies. The findings indicate that tourism development in Lerep Tourism Village has shown progress, particularly in unique tourist attractions and local community participation. However, improvements in accessibility and amenities remain crucial. Supporting factors such as local resource availability and the commitment of local government contribute positively to the village's tourism development. Comprehensive and sustainable development strategy is required to establish Lerep Tourism Village as a leading destination capable of attracting domestic and international tourists. This study recommends enhancing infrastructure, digital promotion, and collaboration among stakeholders to support community-based tourism development.